Association of CSF Alzheimer's disease biomarkers with postoperative delirium in older adults. Issue 1 (17th March 2021) - Fong, Tamara G.; Vasunilashorn, Sarinnapha M.; Gou, Yun; Libermann, Towia A.; Dillon, Simon; Schmitt, Eva; Arnold, Steven E.; Kivisäkk, Pia; Carlyle, Becky; Oh, Esther S.; Vlassakov, Kamen; Kunze, Lisa; et al.
Abstract: Introduction: The interaction between delirium and dementia is complex. We examined if Alzheimer's disease (AD) biomarkers in patients without clinical dementia are associated with increased risk of postoperative delirium, and whether AD biomarkers demonstrate a graded association with delirium severity. Methods: Participants ( n  = 59) were free of clinical dementia, age ≥ 70 years, and scheduled for elective total knee or hip arthroplasties. Cerebrospinal fluid (CSF) was collected at the time of induction for spinal anesthesia. CSF AD biomarkers were measured by enzyme‐linked immunosorbent assay (ELISA) (ADX/Euroimmun); cut points for amyloid, tau, and neurodegeneration (ATN) biomarker status were A  = amyloid beta (Aβ)42  <175 pg/mL or Aβ42/40 ratio <0.07; T  = p‐tau >80 pg/mL; and N  = t‐tau >700 pg/mL. Confusion Assessment Method (CAM) and CAM‐Severity (CAM‐S) were rated daily post‐operatively for delirium and delirium severity, respectively. Results: Aβ42, tau, and p‐tau mean pg/mL (SD) were 361.5 (326.1), 618.3 (237.1), and 97.1 (66.1), respectively, for those with delirium, and 550.4 (291.6), 518.3 (213.5), and 54.6 (34.5), respectively, for those without delirium. Thirteen participants (22%) were ATN positive. Delirium severity by peak CAM‐S [mean difference (95% confidence interval)] was 1.48 points higher (0.29‐2.67), P  = 0.02 among the ATN positive. Delirium in the ATN‐positive group trended toward but did not reach statistical significance (23% vs. 7%, p = 0.10). Peak CAM‐S [mean (SD)] in the delirium group was 7 (2.8) compared to no delirium group 2.5 (1.3), but when groups were further classified by ATN status, an incremental effect on delirium severity was observed, such that patients who were both ATN and delirium negative had the lowest mean (SD) peak CAM‐S scores of 2.5 (1.3) points, whereas those who were ATN and delirium positive had CAM‐S scores of 8.7 (2.3) points; other groups (either ATN or delirium positive) had intermediate CAM‐S scores. Discussion: The presence of AD biomarkers adds important information in predicting delirium severity. Future studies are needed to confirm this relationship and to better understand the role of AD biomarkers, even in pre‐clinical phase, in delirium.